Human cytomegalovirus strain-dependent changes in NK cell recognition of infected fibroblasts. - Cerboni, C; Mousavi-Jazi, M; Linde, A; Söderström, K; Brytting, M; Wahren, B; Kärre, K; Carbone, E (2000)
NK cells play a key role in the control of CMV infection in mice, but the mechanism by which NK cells can recognize and kill CMV-infected cells is unclear. In this study, the modulation of NK cell susceptibility of human CMV (hCMV)-infected cells was examined. We used a human lung and a human foreskin fibroblast cell line infected with clinical isolates (4636, 13B, or 109B) or with laboratory strains (AD169, Towne). The results indicate that all three hCMV clinical isolates confer a strong NK resistance, whereas only marginal or variable effects in the NK recognition were found when the laboratory strains were used. The same results were obtained regardless of the conditions of infection, effector cell activation status, cell culture conditions, and/or donor-target cell combinations. The NK cell inhibition did not correlate with HLA class I expression levels on the surface of the target cell and was independent of the leukocyte Ig-like receptor-1, as evaluated in Ab blocking experiments. No relevant changes were detected in the adhesion molecules ICAM-I and LFA-3 expressed on the cell surface of cells infected with hCMV clinical and laboratory strains. We conclude that hCMV possesses other mechanisms, related neither to target cell expression of HLA-I or adhesion molecules nor to NK cell expression of leukocyte Ig-like receptor-1, that confer resistance to NK cell recognition. Such mechanisms may be lost during in vitro passage of the virus. These results emphasize the differences between clinical hCMV isolates compared with laboratory strains.